Investigations of mechanical behavior in gear pump using design of software - Raghunathan, C.; Manoharan, C. (International Journal of Engineering and Technology, 2014)
This research study focused on the various aspects of tribological phenomenon using design of experiments approach, results are analyzed and compared to evaluate the gear performance. Though lot of research work had been carried out on the hydrodynamic gear under static loads, till date no one consider the parameter say stiffness, damping co-efficient, squeeze film effects and the pressure distribution at various crank angle under dynamic load conditions and its effects on inertia forces of gear pump. It covers sinusoidal load, journal speed, face width and mass flow rate with respect to variations in oil film thickness. Frictional test rig was used to measure the frictional force and oil film thickness at various crank angles for every three minutes at an interval of every 15 degree crank angle. The response surface methodology (RSM) analysis shows appreciable increases in respect of performances in mass flow rate, face width, speed and loading against the Taguchi design of experiment results whereas the film thickness is almost same in both RSM and Taguchi design of experiment results. Particular attention is given in this research exertion to learn how the variation in gear dimensions influences the characteristics of the hydrodynamic gear pump. Keywords: Hydrodynamic Gear Pump, Oil Film Thickness, Mathematical Modeling, Taghuchi and RSM, Eddycurrent Cap Sensor.